Enhancing pharmacy education through Collaborative Online Integrated Learning (COIL): a cross-cultural pilot study between pharmacy students of Malaysia and the Philippines - Farida Islahudin; Mohd Makmor-Bakry; Siti Azdiah Abdul Aziz; Erwin Martinez Falle; Fatima May R Tesoro; Jacqueline Padilla; Chandini Menon Premakumar (Penerbit Universiti Kebangsaan Malaysia, 2025)
Collaborative Online Integrated Learning (COIL) is a cost-effective approach to enhancing student’s professional competency by exposing them to diverse cultural environments. Together with Problem-Based Learning (PBL), which engages students in active, scenario-based problem solving, this method further develops critical thinking and intercultural competence. The COVID-19 pandemic enabled COIL to be explored further in pharmacy education due to travel restrictions. The aim of the study was to compare the effects on perception, knowledge and participation before and after an anti-infective COIL module. Students from two international faculties from Malaysia and the Philippines were included in the study. Incomplete questionnaires were excluded. A total of 85 students were involved in the study, of whom 47 (55.3%) were year 4 Malaysian pharmacy students, and 38 (44.7%) were year 3 Philippine pharmacy students. An overall improvement in their perception of enjoying (t=- 13.4, df (82), p<0.001) and feeling confident when interacting with students from different countries was observed (t=-17.5, df (82), p<0.001, respectively). Similarly, an overall improvement in total anti-infective knowledge scores between baseline and post-COIL was demonstrated (t=-12.5, df=82, p<0.001). Post-COIL assessments showed that 20 (24.1%) students reported being active, while 63 (75.9%) reported being very active during discussions on socio-cultural responses to anti-infectives. In discussions on rational anti-infective use, 4 (4.8%) students reported feeling neutral, 28 (33.7%) were active, and 51 (61.4%) were very active. COIL, paired with PBL, was an effective method for improving intercultural exposure and knowledge, indicating its potential for incorporation into pharmacy schools worldwide.